FRI0525 INFLUENZA VACCINATION COMPLIANCE AND RESPONSE IN AUTOIMMUNE INFLAMMATORY RHEUMATIC DISEASE PATIENTS: A COHORT STUDY. (2nd June 2020) - Kumar, P.; Trebbien, R.; Leutscher, P. C.; Strandbygaard, L.; Rasmussen, C.
Abstract : Background: Patients diagnosed with autoimmune inflammatory rheumatic diseases (AIIRD) have higher risk of developing infections due to immunological dysfunction and immunosuppressive treatments. Current guidelines recommend annual influenza vaccination to reduce infection risk in this group of patients. However, vaccination response in these patients is uncertain. Objectives: To study influenza vaccination compliance and response in a Danish AIIRD patient population. Methods: AIIRD patients on biological treatment ± synthetic disease-modifying antirheumatic drugs (sDMARDs) in our department of rheumatology and registered in the Danish Rheumatology database (DANBIO) were included in the current study. The patients were encouraged to be vaccinated against influenza in the 2018/19 winter season. Status of influenza vaccination for the period of 1.9.2018 to 31.12.2018 was reviewed in each patient using the Danish Vaccination Register (DDV) and Danish Electronic Medicine Module (FMK). Patient data were collected by review of the medical files. Serum samples from each patient were collected on two occasions: 1) from 1.6.2017 to 15.5.2018 (before vaccination) and 2) from 1.11.2018 to 1.3.2019 (after vaccination), respectively. Antibody titers against the three antigens included in the trivalent 2018/2019 seasonal influenza vaccine were measured by hemagglutination inhibition assay followed by determination of geometric mean titers (GMT). Results: Among a total of 226 study eligible AIIRD patients, 111 (49%) had been influenza vaccinated. In the remaining group of 115 (51%) non-vaccinated patients, 50 were randomly contacted by telephone to ensure the accuracy of DDV registration. All 50 confirmed non-vaccinated status. Median age of vaccinated group was 65 years while of non-vaccinated group was 57 years (p≤0.00001). Median GMT increased from 10 to 22 in the group of vaccinated patients versus from 6 to 10 in the group of non-vaccinated patients (p<0.0001). GMT increased ≥2-fold in 79 (71%) of 111 influenza vaccinated in comparison to 60 (52%) of 115 non-vaccinated patients (p≤0.003). Among influenza vaccinated patients, median age of responders (≥2-fold increase in GMT) was 66 years versus non-responders 63 years (p=0.3). In the influenza vaccinated group, ≥2-fold increase in GMT was seen in 51 (73%) of 70 patients receiving methotrexate compared to 28 (68%) of 41 in patients not receiving methotrexate (p=0, 6). Conclusion: Only half of the patients were compliant to the vaccination recommendations in the 2018/2019 influenza season despite the information campaign. Response rate of influenza vaccination (≥2-fold GMT increase) was 71% in AIIRD patients receiving immunosuppressive treatments. In contrast to other studies, concurrent methotrexate treatment did not attenuate serological response of influenza vaccination. We are still exploring the causes of increased influenza antibody titers in non-vaccinated group. References: [1] Kapetanovic MC, Kristensen LE, Saxne T, et al. Impact of anti-rheumatic treatment on immunogenicity of pandemic H1N1 influenza vaccine in patients with arthritis. Arthritis Res Ther 2014;16:R2. [2] Hua C, Barnetche T, Combe B, et al. Effect of methotrexate, anti-tumor necrosis factor α, and rituximab on the immune response to influenza and pneumococcal vaccines in patients with rheumatoid arthritis: a systematic review and meta-analysis. Arthritis Care Res 2014;66:1016–26. [3] Furer V, et al. 2019 update of EULAR recommendations for vaccination in adult patients with autoimmune inflammatory rheumatic diseases. Ann Rheum Dis 2020;79:39–52. doi:10.1136/annrheumdis-2019-215882 Disclosure of Interests: None declared